Kepuasan pernikahan dengan depresi pada kelompok wanita menikah yang bekerja dan tidak bekerja - Erni Pujiastuti; Sofia Retnowati (Universitas Ahmad Dahlan, 2004)
The purpose of this research was to find out correlation between the marriage satisfaction with depression of 118 married women (61 working women and 57 housewife from age 20 to 50 whom lived at Taman Bumyagara Housing, Bantargebang, Bekasi by scale measurement method The Beck's Depression Inventory (BDI) and marriage satisfaction scale.It was found that there was no marriage satisfaction different between those marriage-working-women and those housewife (t = -0,148; p > 0,05), and also there was no depression difference betweeen both of them (t = 1,267; p > 0,05)